MANFAAT PEMBERDAYAAN YANG DILAKUKAN BANK SAMPAH INDUK DI KOTA BANDUNG - Jaya, Ratnawati Kusuma; Machdum, Sari Viciawati (Social Welfare Study Program, 2021)
Abstract. Waste Bank is one of the instruments in community participation-based waste management which is expected to be able to contribute to the process of reducing and handling waste in Indonesia. However, the waste bank (unit) faces many obstacles in the field. To face these challenges, the Government of Indonesia recommends that every Regency/City have a Main Waste Bank. This study discusses the impacts of the Bandung City Induk Waste Bank, the Resik Waste Bank of Bandung City Regional Company (PD), in an effort to reduce and handle waste to support sustainable development through community empowerment. This research was conducted using a qualitative research approach. Methods of collecting data through in-depth interviews and observation. The results of the study indicate that the Resik Waste Bank performs various empowerment roles through facilitative and educational roles and abilities that are carried out which ultimately provide benefits to the community and members of the waste bank unit both in terms of economic, environmental, and social development. These benefits contribute to the social dimensions of sustainable development, namely poverty reduction, participatory development, and consensus building.Keywords: Solid waste management; sustainable development; community development; empowerment; waste bank.Abstrak. Bank Sampah merupakan salah satu instrumen dalam pengelolaan sampah berbasis partisipasi masyarakat yang diharapkan mampu berkontribusi dalam proses pengurangan dan penanganan sampah di Indonesia. Namun, bank sampah (unit) mengalami banyak kendala di lapangan. Untuk menghadapi tantangan tersebut, Pemerintah Indonesia menyarankan agar setiap Kabupaten/Kota memiliki Bank Sampah Induk. Penelitian ini membahas tentang manfaat pemberdayaan yang dilakukan Bank Sampah Induk di Kota Bandung yang bertujuan untuk mengetahui upaya pengurangan dan penanganan sampah untuk mendukung pembangunan berkelanjutan. Penelitian ini dilakukan menggunakan pendekatan penelitian kualitatif. Metode pengumpulan data melalui wawancara mendalam dan observasi. Hasil penelitian menunjukkan bahwa Bank Sampah Resik melakukan berbagai peran pemberdayaan melalui peran dan kemampuan fasilitatif dan edukasional yang dilakukan yang akhirnya memberikan manfaat kepada masyarakat dan anggota bank sampah unitnya baik manfaat pada perkembangan ekonomi, lingkungan, dan sosial. Manfaat tersebut berkontribusi pada dimensi sosial dalam pembangunan berkelanjutan yakni poverty reduction, participatory development dan consensus building. Kata kunci: Pengelolaan sampah; pembangunan berkelanjutan; pengembangan masyarakat; pemberdayaan; bank sampah.